1982
DOI: 10.1038/298481a0
|View full text |Cite
|
Sign up to set email alerts
|

Epifluorescent microscopic evidence for maternal inheritance of chloroplast DNA

Abstract: Maternal inheritance of chloroplast genes occurs in the isogamous green alga Chlamydomonas reinhardii. It has been shown using biochemical techniques that the chloroplast DNA of male origin is preferentially lost by 6 h after mating. DNAs in the chloroplast are organized by proteins into about 10 chloroplast nucleoids. Therefore, if chloroplast DNA in zygotes is preferentially destroyed, the disappearance of chloroplast nucleoids from male gametes should be observable during zygote formation by high resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
91
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(101 citation statements)
references
References 9 publications
8
91
0
2
Order By: Relevance
“…DAPI fluorescence (Fig. 7B, a, c, e, and g) confirmed previous reports (Kuroiwa et al, 1982); 1 h after cell fusion the zygote contained cell and chloroplast nuclei derived from both parents, but at 6 h it lacked the male-derived chloroplast nuclei and had a single, fused cell nucleus.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…DAPI fluorescence (Fig. 7B, a, c, e, and g) confirmed previous reports (Kuroiwa et al, 1982); 1 h after cell fusion the zygote contained cell and chloroplast nuclei derived from both parents, but at 6 h it lacked the male-derived chloroplast nuclei and had a single, fused cell nucleus.…”
Section: Discussionsupporting
confidence: 75%
“…When they encounter cells of the opposite mating type, they recognize their partner, begin to agglutinate, and then fuse to become zygotes. After zygote formation, a number of events ensue, including preferential digestion of malederived chloroplast nuclei (Kuroiwa et al, 1982), nuclear fusion (Cavalier-Smith, 1970;Kuroiwa et al, 1982), flagellar degeneration, and zygospore formation (Cavalier-Smith, 1976). All functional proteins and their mRNAs directly involved in these phenomena are thought to be synthesized only after cell fusion (Kuroiwa et al, 1983;Kuroiwa, 1991).…”
mentioning
confidence: 99%
“…These observations validate the necessity to eliminate paternal mt (cp) DNA before the destruction of mt (cp) structures. Active digestion of uniparental mt (cp) DNA has been observed in various species, including higher plants (2,21), algae (13,16), and slime mold (58,59). Also, in these cases, mt (cp) DNA molecules are digested, whereas the structures of mitochondria or chloroplasts remain apparently intact, which might be necessary to avoid the potential hazard caused by sexual recombination of mt (cp) genomes in these species.…”
Section: Discussionmentioning
confidence: 99%
“…In C. reinhardtii, 80-90 copies of the cp genome are compacted into 5-8 cp nucleoids (15). In 1982, Kuroiwa et al (16) found that mtϪ cp nucleoids disappear preferentially in young zygotes 50 min after mating. In 1998, the preferential disappearance of mtϪ cp nucleoids was observed in a living zygote (17).…”
mentioning
confidence: 99%
“…Initially, nucleoids were defined morphologically as DNA-containing foci visualized inside mitochondria (Kuroiwa, 1982;Nass et al, 1965;Stevens, 1982) or chloroplasts (Eva and Chiang, 1984;Kuroiwa et al, 1982). Later, mitochondrial nucleoids were isolated at a defined density in gradient centrifugation and appeared to retain their morphological structure in vitro (Dai et al, 2005;Miyakawa et al, 1987;Newman et al, 1996;Suzuki et al, 1982).…”
Section: Introductionmentioning
confidence: 99%